Anthropometric Variables in the Identification of High-performance Volleyball Players - Abdullah, Prof. Madya Dr. Mohamad Razali (Springer Science and Business Media Deutschland GmbH, 2021)
In this chapter, we delve into the importance of certain anthropometric- and age-related variables in the detection of high- performance players during an indoor volleyball tournament. It is demonstrated that high- performance players in this sport are essentially taller, relatively younger, as well as slightly heavier, whilst huge body size coupled with higher age is found to be associated with low performance in the sport of men indoor volleyball . Moreover, an ANN-based classification model was found to be effective in the identification of the performance classes of the players. © 2021, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.